Recontextualising UTAUT2 for Voluntary Religious Giving: Evidence from Indonesia’s Digital Zakat - Efri Andini; Tissa Aulia Damayanti; M. Gunawan Azhar; Roky Apriansyah (Universitas Muhammadiyah Surakarta, 2026)
Indonesia is home to the largest Muslim community on earth and to a zakat base estimated above IDR 327 trillion, yet the funds actually collected amount to less than fifteen percent of that ceiling. Digital zakat services have multiplied in recent years, but their take-up among muzakki remains patchy, and what actually motivates voluntary religious giving through online channels is still poorly mapped. The current research broadens the second-generation of Unified Theory of Acceptance and Use of Technology by adding three constructs that become essential once the technology mediates an act of worship rather than an ordinary purchase: zakat literacy, Islamic religiosity, and trust in zakat institutions. Employing a quantitative approach, explanatory devise, survey data were collected from 373 Indonesian Muslims via a purposive online questionnaire and analysed with Partial Least Squares Structural Equation Modelling in SmartPLS 4. The findings show that the exogenous constructs jointly and positively shape the intention to give zakat through digital means (p < 0.01), with effort expectancy, trust in zakat institutions, and facilitating conditions standing out as the leading drivers. Overall, the model accounts for a substantial share of the variance in behavioural intention, and discriminant validity is upheld under the Fornell-Larcker, cross-loading, and Heterotrait-Monotrait criteria. The contribution is a context-adjusted acceptance model showing that, for voluntary religious giving, technological readiness works in concert with, not separately from, spiritual conviction and institutional credibility. The discussion draws out implications for amil zakat bodies, fintech developers, and regulators aiming to build digital zakat ecosystems that are more trustworthy, easier to use, and demonstrably Sharia-compliant.